A condition assessment method for time-variant structures with incomplete measurements. (June 2015) - Ding, Y.; Zhao, B.Y.; Wu, B.; Xu, G.S.; Lin, Q.; Jiang, H.B.; Miao, Q.S.
Abstract: The structural damage incurred in a seismic event is always time-variant. In this paper, a new time-variant structural system identification method is proposed based on a two-stage strategy and incomplete structural acceleration responses. In the first stage, an external excitation identification method is developed for a time-variant structural system. The unknown structural response could be re-constructed with the average acceleration discrete algorithm in this stage. In the second stage, structural parameter is identified and updated with a reduced extended Kalman filter which can improve the computational effort. The re-constructed structural response and identified external excitation are used in the second stage for the damage identification and model updating. The proposed method is validated numerically with the simulation of a fifteen-storey shear frame structure subject to earthquake excitation. A model of a fourteen-storey concrete shear wall building was also studied experimentally with shaking table tests to further validate the proposed method. This shear wall building has a two-storey steel frame on top with base isolation. Both the stiffness of the model and the interface force in the isolator at the bottom of the steel frame during the seismic excitation were estimated with the proposed method. Results from both numerical simulations and laboratory tests indicate that the proposed method can be used to identify structural parameters and external excitations effectively based on a few number of polluted structural acceleration measurements. Highlights: A method for identification of time-variant structures is proposed. A new two-stage strategy is proposed for the identification of load and parameter. Force identification method is improved for the time variant system. A shake table test of a shear wall structure is to validate the method.